2019
DOI: 10.1093/cid/ciz540
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone and Multidrug Resistance Predicts Failure of Antibiotic Prophylaxis of Spontaneous Bacterial Peritonitis

Abstract: Background The efficacy of antibiotic prophylaxis to prevent spontaneous bacterial peritonitis (SBP) in patients colonized with multidrug-resistant organisms (MDROs) is unknown. We evaluated the effectiveness of fluoroquinolone-based SBP prophylaxis in an era and area of frequent antibiotic resistance. Methods This is a prospective observational study in patients with liver cirrhosis and an indication for fluoroquinolone-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 26 publications
1
40
1
Order By: Relevance
“…Most recently, the CANONIC study group reported a high and increasing prevalence of MDROs in culture-positive infections in patients with decompensated cirrhosis all over Europe ( 15 ). We have recently shown in a prospective cohort study that the effectiveness of SBP prophylaxis might be critically reduced in an environment of highly prevalent MDROs ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, the CANONIC study group reported a high and increasing prevalence of MDROs in culture-positive infections in patients with decompensated cirrhosis all over Europe ( 15 ). We have recently shown in a prospective cohort study that the effectiveness of SBP prophylaxis might be critically reduced in an environment of highly prevalent MDROs ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is an ongoing debate as to whether to extend the indication for antibiotic prophylaxis in cirrhosis: so far, it has been recommended for patients with ascites at high risk for SBP (primary prophylaxis) or with prior SBP (secondary prophylaxis) [ 5 , 6 ]. We observed higher risk of prophylaxis failure in patients with known status of multidrug-resistant bacteria (MDRO) and a recent meta-analysis reported a reduced efficacy of quinolone prophylaxis to prevent SBP over the last decades [ 8 , 23 ], while others have observed an alarming increase of MDRO in patients with cirrhosis over time [ 24 , 25 ]. Yet, Moreau et al [ 7 ] observed in a recently published, large randomized controlled trial significantly reduced overall infection rates in cirrhotic patients in general and a better overall survival in those with low ascites protein content.…”
Section: Discussionmentioning
confidence: 99%
“…Primary or secondary antibiotic prophylaxis with quinolones was started at baseline in all patients at the time of study inclusion, either with norfloxacin 400 mg once daily or ciprofloxacin 500 mg once daily; the choice between both agents was made at the treating physicians’ discretion. Patients were part of the observational study on MDRO prevalence and occurrence of MDRO under SBP prophylaxis; details on the study protocol and clinical outcome are reported elsewhere [ 8 ]. In the present sub-analysis of this study, patients were included if they were willing to provide serial stool samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these recommendations also emphasize that empirical antibiotic strategies need to be tailored according to local microbiological epidemiology. Notably, a previous study showed that the use of carbapenems was the only strong independent predictor for the emergence of MDR bacteria, including carbapenem-resistant MDR bacteria, 14 which represents a substantial global health and economic threat, and simultaneously increase the risk of death and the length of stay in patients with BSI. 15 Hence, it should be noted that carbapenems-sparing therapy options are urgently necessary to reduce the continuing prevalence of MDR bacteria 16 and consequent economic threat.…”
Section: Introductionmentioning
confidence: 99%